Manipulating regulatory T cells: a promising strategy to treat autoimmunity. (November 2015) - Zhang, Dunfang; Tu, Eric; Kasagi, Shimpei; Zanvit, Peter; Chen, Qianming; Chen, WanJun
CD4 + CD25 + Foxp3 + regulatory T cells (Treg cells) are extremely important in maintaining immune tolerance. Manipulation of Treg cells, especially autoantigen-specific Treg cells is a promising approach for treatments of autoimmune disease since Treg cells may provide the advantage of antigen specificity without overall immune suppression. However, the clinical application of Treg cells has long been limited due to low numbers of Treg cells and the difficulty in identifying their antigen specificity. In this review, we summarize studies that demonstrate regression of autoimmune diseases using Treg cells as therapeutics. We also discuss approaches to generate polyclonal and autoantigen-specific Treg cells in vitro and in vivo . We also discuss our recent study that describes a novel approach of generating autoantigen-specific Treg cells in vivo and restoring immune tolerance by two steps apoptosis–antigen therapy.